Letramento informacional em bibliotecas do Instituto Federal do Espírito Santo: o trabalho do bibliotecário frente às demandas e necessidades informacionais dos estudantes - Kelly Rita de Azevedo (2020)
It is a research that aims to identify the role of the library and the librarian in the development of information literacy of Ifes' students, in face of the demands and needs of information present in their daily lives. The responsibility that the librarian has to know and plan activities for the users served by these information units needs to be known and understood, mainly due to the fact that the education model existing in this institution, differs from the educational standards known in Brazil. Methodologically, the research was classified as descriptive and established in its design the case study as a method; it established as a clipping two libraries belonging to the Ifes' Santa Teresa and Vitória campuses. The analysis of empirical data was developed with a quantitative and qualitative approach, with students and librarians as the unit of analysis. The questionnaire and semi-structured interview were used as instruments. Seven librarians participated in the research, two librarians from the Santa Teresa campus and five from the Vitória campus. 4,235 questionnaires were sent to students over eighteen years of age regularly enrolled in the face-to-face courses offered by the Santa Teresa and Vitória campuses. The Federal Institute of Espírito Santo (Ifes) is an institution belonging to the Federal Network of Professional, Scientific and Technological Education that offers public professional education. Integrating teaching, research and extension, it groups, in the same space, students in different teaching modalities. This characteristic gives the institution and its libraries a status of novelty with regard to the profile of its students. Access to information, caused by the availability of supports, requires the librarian to take a new professional stance, as he is faced with a period when changes in his practice become necessary, in which collaborative work between librarians, the pedagogical team and teachers is essential, to assist and educate the library user in the development of students' information literacy. Information needs have changed and continue to evolve, as the resources to access them. The results showed that librarians have partial knowledge about the attribute of information literacy and its importance in the development of student autonomy in the use of information through the activities and services offered by the library through training for the user. However, even though aware of this importance, there is no specific action by librarians to develop students' information literacy. The absence of a project aimed at training users in libraries, coupled with the lack of knowledge of the educational role of the librarian by the pedagogical team and teachers, contributes to the lack of collaborative work among these agents, aiming at the development of access, search, retrieval and use of information by students. Such factors contribute for the students to ignore the potential of activities of the librarian, considering that many did not have the opportunity to experience a library with the presence of librarians. The research sheds light on the path that needs to be taken by the librarian so that he can be recognized as a professional linked to education, not only by the student, in a more direct way and that the library can be seen as a space for education and generation of knowledge.